Examining systemic differences in mortality after hip repair: a comparative analysis of 30- and 180-day adjusted mortality rates in five health systems. - Estupiñán-Romero, Francisco; Royo-Sierra, Santiago; González-Galindo, Javier; Wei, Jinru; Sawaya, Tania; Wilder, Astrid Van; Bai, Yu Qing; Rehnberg, Clas; Janlöv, Nils; Sund, Reijo; Wodchis, Walter P; Papanicolas, Irene; et al. (European Journal of Public Health, 2025)
Outcomes after a hip repair in the older adult population are highly dependent on patients' characteristics. However, contextual factors such as the hospital of treatment may have an impact not sufficiently studied. We aimed to elicit the effect of hospital providers on all-cause-adjusted mortality rates after hip fracture repair. Observational study on virtually all potentially eligible hip fracture patients treated in 2240 hospitals from Ontario (Canada), Aragon (Spain), Finland, Sweden, and the USA (40 states). The primary endpoint was the risk-adjusted all-cause mortality after hip repair measured 30 days and 180 days after surgery. Following a federated approach, GAMM-logit models were run for each region. Median odds ratio (MOR) were estimated to elicit the variation at hospital level. The study included 535 519 hip repairs. The overall predicted 30-day adjusted mortality rate was 40.5 per 1000 hip repair episodes; 136.3 per 1000 hip repair episodes in the 180-day adjusted mortality rate. 30- and 180-day adjusted mortality rates were larger within the regions than across regions. Variance in patients' mortality at the hospital provider accounted for MOR: 1.43 in 30-day mortality and MOR: 1.35 in 180-day mortality. Beyond differences in the individual risk of death, our study found wide systemic variations in mortality rates in older adult patients exposed to hip fracture repair attributable to the hospital of treatment. Our results call for a reorientation of care pathways after hip repair in frail patients, both in the short- and the long-term.